Accumulation of cesium in glue balls of spiders' orb webs. (13th April 2020) - Zhao, Yue; Morita, Masato; Sakamoto, Tetsuo
Abstract : Spiders capture prey by applying sticky coating substances to the spiral line of their orb webs. The main constituents of these sticky substances are glycoproteins and salts. This sticky substance is an intelligent material. Salt plays a key role regarding the properties of the sticky substance. Spiders typically weave a new orb webs by recycling used orb webs, and salts, typically salts of the alkali metals sodium and potassium, were therefore assumed to be recycled in this process. Here, we fed cesium (Cs) carbonate (which is an alkali metal salt) to spiders ( Araneus ventricosus ) to test this hypothesis. After feeding, we mapped the sticky substance in the spiders' orb web using an in‐house time‐of‐flight secondary ion mass spectrometer with high lateral resolution. The results showed that Cs ion was ingested and integrated into the sticky substance, and it showed properties similar to those of sodium ion and potassium ion.